The Efficacy of Synchronous Combination of Chemotherapy and EGFR TKIs for the First-Line Treatment of NSCLC: A Systematic Analysis. - Han Yan; Huihui Li; Qin Li; Pengfei Zhao; Wei Wang; Bangwei Cao (PLoS ONE, 2015)
The combination of chemotherapy and epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) currently has become the hotspot issue in the treatment of non-small lung cancer (NSCLC). This systematic review was conducted to compare the efficacy and safety of the synchronous combination of these two treatments with EGFR TKIs or chemotherapy alone in advanced NSCLC.EMBASE, PubMed, the Central Registry of Controlled Trials in the Cochrane Library (CENTRAL), Chinese biomedical literature database (CNKI) and meeting summaries were searched. The Phase II/III randomized controlled trials were selected by which patients with advanced NSCLC were randomized to receive a combination of EGFR TKIs and chemotherapy by synchronous mode vs. EGFR TKIs or chemotherapy alone.A total of six randomized controlled trials (RCTs) including 4675 patients were enrolled in the systematic review. The meta-analysis demonstrated that the synchronous combination group of chemotherapy and EGFR TKIs did not reach satisfactory results; there was no significant difference in overall survival (OS), time to progression (TTP) and objective response rate (ORR), compared with monotherapy (OS: HR = 1.05, 95%CI = 0.98-1.12; TTP: HR = 0.94, 95%CI = 0.89-1.00; ORR: RR = 1.07, 95%CI = 0.98-1.17), and no significant difference in OS and progression-free survival (PFS), compared with EGFR TKIs alone (OS: HR = 1.10, 95% CI = 0.83-1.46; PFS: HR = 0.86, 95% CI = 0.67-1.10). The patients who received synchronous combined therapy presented with increased incidences of grade 3/4 anemia (RR = 1.40, 95% CI = 1.10-1.79) and rash (RR = 7.43, 95% CI = 4.56-12.09), compared with chemotherapy, grade 3/4 anemia (RR = 6.71, 95% CI = 1.25-35.93) and fatigue (RR = 9.60, 95% CI = 2.28-40.86) compared with EGFR TKI monotherapy.The synchronous combination of chemotherapy and TKIs is not superior to chemotherapy or EGFR TKIs alone for the first-line treatment of NSCLC.